Study of D J meson decays to D+π-, D0π+ and D*+π- final states in pp collisions - Aaij, Roel; Adeva, B.; Adinolfi, M.; Aquines Gutiérrez, Osvaldo; Bachmann, Sebastian; Bien, Alexander; Blouw, Johan; Britsch, Markward; De Cian, Michel; Di Canto, Angelo; Dordei, Francesca; Färber, Christian; et al. (Journal of high energy physics, 2013)
Abstract: A study ofD+π−,D0π+andD∗+π−final states is performed usingppcollisiondata, corresponding to an integrated luminosity of 1.0 fb−1, collected at a centre-of-massenergy of 7 TeV with the LHCb detector. TheD1(2420)0resonance is observed in theD∗+π−final state and theD∗2(2460) resonance is observed in theD+π−,D0π+andD∗+π−final states. For both resonances, their properties and spin-parity assignments are obtained.In addition, two natural parity and two unnatural parity resonances are observed in themass region between 2500 and 2800 MeV. Further structures in the region around 3000MeV are observed in all theD∗+π−,D+π−andD0π+final states.
Im Titel sind "+", "-" und "0" hochgestellt und "J" tiefgestellt
LHCb Collaboration: R. Aaij, B. Adeva; M. Adinolfi, O. Aquines Gutierrez, S. Bachmann, A. Bien, J. Blouw, M. Britsch, M. De Cian, A. Di Canto, F. Dordei, C. Färber, M. Fontana, E. Gersabeck, O. Grünberg, S. Hansmann-Menzemer, T. Hartmann, A. Jaeger, K. Kreplin, G. Krocker, B. Leverington, C. Linn, J. Marks, M. Meissner, T. Nikodem, D. Popov, M. Schmelling, P. Seyfert, S. Stahl, J. van Tilburg, U. Uwer, D. Volyanskyy, C. Voß, H. Voss, R. Waldi, S. Wandernoth, D. Wiedner, M. Zavertyaev, A. Zhelezov und weitere 611
Gesehen am 21.04.2021